2019
DOI: 10.1186/s12879-018-3598-3
|View full text |Cite
|
Sign up to set email alerts
|

Carriage rates and risk factors during an outbreak of invasive meningococcal disease due to Neisseria meningitidis serogroup C ST-11 (cc11) in Tuscany, Italy: a cross-sectional study

Abstract: BackgroundDuring 2015–2016 an outbreak of invasive meningococcal disease due to N. meningitidis serogroup C ST-11 (cc11) occurred in Tuscany, Italy. The outbreak affected mainly the age group 20–30 years, men who have sex with men, and the area located between the cities of Firenze, Prato and Empoli, with discos and gay-venues associated-clusters. A cross-sectional-survey was conducted to assess the prevalence and risk factors for meningococcal-carriage, in order to address public health interventions.MethodsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Interestingly, we did not observe any non-groupable meningococci, although non-encapsulated N. meningitidis are frequently found among carriers according to the literature [ 26 , 40 42 ].…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Interestingly, we did not observe any non-groupable meningococci, although non-encapsulated N. meningitidis are frequently found among carriers according to the literature [ 26 , 40 42 ].…”
Section: Discussionmentioning
confidence: 46%
“…A cross-sectional study in Tuscany, Italy, found a carriage prevalence of 4.8% in individuals aged 11-45 years presenting at immunization clinics. Among the age group 31-45 years, the carriage prevalence was 2.4% (20/ 828), while it was 9% (37/434) in the age group 20-30 years [26]. A study conducted in 2014 in Hajj pilgrims with a mean age of 50 years found 1.3% meningococcal carriers in individuals originating from low endemic countries, while 8.9% of pilgrims from high endemic regions (sub-Saharan meningitis belt) were tested positive for N. meningitidis [27].…”
Section: Discussionmentioning
confidence: 88%
“…As already published [19], 110 carriage samples resulted positives for N . meningitidis and 85 of them were cultivated in vitro.…”
Section: Introductionmentioning
confidence: 66%
“…Ethical approval was obtained by the Regional Ethic Committee of Tuscany (registration no. 965) [19]. A written informed consent was signed by all the participants and by the parents/legal guardians of subjects aged less than 18 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation